Performing by the Book? Musical Negotiations between Text and Act - Forment, Bruno 1978- (Leuven Leuven University Press, 2024)
The challenges and limits for musicians dealing with texts.To perform a musical score implies the transformation of a symbolically coded text into vibrant sound. In Performing by the Book? a carefully selected cadre of artist-researchers dissects this delicate act in critical ways. Offering first-hand insights into the notational, structural and interpretative challenges faced by musicians in dealing with texts of all kinds, the chapters traverse the spectrum between the Middle Ages and the age of Stockhausen. In a harmonious blend of scholarly allure and individual artistry, free from academic obfuscation, the contributors keep a keen eye on the limits of interpretation, both in terms of the interpretative process itself and of the balance between textual faithfulness and artistic autonomy. This comprehensive volume is an indispensable guide for everyone interested in the relationship between musical performance and texts.Contributing authors: Niels Berentsen (Haute école de musique de Genève-Neuchâtel (HES-SO) / conductor of Diskantores), Björn Schmelzer (artistic director of Graindelavoix / independent researcher), Jonathan Ayerst (freelance organist and improviser), Elizabeth Dobbin (Le Jardin Secret / Haute école de musique de Genève (HES-SO)), Camilla Köhnken (freelance pianist-researcher / Bern Academy of the Arts), George Kennaway (cellist, conductor, teacher, publisher and musicologist / University of Leeds), Kate Bennett Wadsworth (cellist / Guildhall School of Music and Drama), Nir Cohen-Shalit (conductor and independent researcher), Xiangning Lin (pianist / Yong Siew Toh Conservatory of Music, National University of Singapore), Clare Lesser (independent performer, musicologist and composer).
FRIS
1
Keywords: Warburg, Aby; Bach, Johann Sebastian; Beethoven, Ludwig van; Czerny, Carl; Liszt, Franz; Schumann, Robert; Ravel, Maurice; Poe, Edgar Allan; Stockhausen, Karlheinz; Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Historically informed performance; Choral music; Notation; Improvisation; Freedom; Text; Air; Concerto; Keyboard music; Orchestral music; Conducting; Piano; Cello